The Sustainability of Livelihoods of Villages around the Tin Mine in Bangka Islands - Sulista, Sulista (Research and Development Agency Ministry of Home Affairs, 2019)
Massive tin mining activities in Bangka Belitung Islands Province have caused a detrimental effect that reduces the livelihoods of the people living around the mining area. On the other hand, there has been a shift in livelihoods from agrarian communities to mining communities that increase anxieties on the livelihoods in the future. The purpose of this study is to obtain information about the sustainability of the switched people livelihoods which concentrated in villages around the tin mining area. The study utilized qualitative methods, collected data through interviews and focus group discussions on community leaders, village government officials, and mining actors to analyze aspects of vulnerability and household livelihood strategies based on a sustainable livelihood framework. The results of the study reveal that household groups that work with mining owners and mining tailings have the most vulnerable livelihood resources because their main source of income from tin mining activities is only able to meet their daily needs. Furthermore, the group has very limited land and social relationships that rely solely on elements of kinship and moneylender services when faced with financial difficulties. However, most of these households began to respond to the end of the post-tin economy in the pepper plantation and trade sub-sector. In addition, business opportunities in the sub-sector of livestock, horticulture, and capture fisheries for coastal villages have been utilized by mining owners as the alternative livelihoods.